Anion Complexation Studies of 3-Nitrophenyl-Substituted Tripodal Thiourea Receptor: A Naked-Eye Detection of Sulfate via Fluoride Displacement Assay - Emami Khansari, Maryam (ACS Omega, 2017)
[Image: see text] A thiourea-based tripodal receptor L substituted with 3-nitrophenyl groups has been synthesized, and the binding affinity for a variety of anions has been studied by (1)H NMR titrations and nuclear Overhauser enhancement spectroscopy experiments in dimethyl sulfoxide-d(6). As investigated by (1)H NMR titrations, the receptor binds an anion in a 1:1 binding mode, showing the highest binding and strong selectivity for sulfate anion. A competitive colorimetric assay in the presence of fluoride suggests that the sulfate is capable of displacing the bound fluoride, showing a sharp visible color change. The strong affinity of L for sulfate was further supported by UV–vis titrations and density functional theory (DFT) calculations. Time-dependent DFT calculations indicate that the fluoride complex possesses a different optical absorption spectrum (due to charge transfer between the fluoride and the surrounding ligand) than the sulfate complex, reflecting the observed colorimetric change in these two complexes. The receptor was further tested for its biocompatibility on primary human foreskin fibroblasts and HeLa cells, exhibiting an excellent cell viability up to 100 μM concentration.